PERAN SISTEM INFORMASI PELAYANAN PEMBAYARAN PAJAK DALAM MENINGKATKAN EFEKTIVITAS WAJIB PAJAK - wafa, m azimul; Wafa, Mohammad Azimul; Furqon, Imahda Khoiri ("LAWSUIT" Jurnal Perpajakan, 2024)
Tax information systems, such as e-Filing and e-Billing, are important innovations in modernizing tax administration in Indonesia. This study aims to analyze the role of these systems in improving taxpayer compliance. The method used is descriptive qualitative with a case study approach, using secondary data from official reports and scientific publications. The results show that e-Filing makes it easier to report tax returns online, reduces administrative errors, and speeds up the reporting process. Meanwhile, e-Billing facilitates electronic tax payments, increases efficiency, and ensures the accuracy of transaction data. Nevertheless, the implementation of these systems faces challenges such as low digital literacy, technical constraints, and access gaps in remote areas. These factors hinder equitable adoption, especially among MSMEs and rural communities. This study concludes that e-Filing and e-Billing systems contribute significantly to improving taxpayer compliance, provided that these challenges can be overcome through digital education, infrastructure improvements, and technical support. Thus, these systems not only support the achievement of tax revenue targets, but also increase taxpayers' confidence in the transparency and accountability of tax services in Indonesia.